Pelatihan Pembuatan Filter Air Sederhana Skala Rumah Tangga di Kelurahan Gambut - Norsita Agustina; Chandra Chandra; Zuhrupal Hadi; Ahmad Fauzan; Eddy Rahman (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Clean water is one of the basic needs for human life. Making simple raw water treatment equipment using a filtration system is expected to help the community to process dirty water into raw water on the scale of household needs. Poor water quality will affect the health of existing residents. There is a need for innovation in the manufacture of water filters in order to improve the quality of water for daily needs so that it becomes a more useful product or material. The method used in achieving the goal is to provide training in making simple water filters. The right method used for processing turbid water from household dug wells into clean water in an area is to use the multilevel filter method. This filtering process is to remove suspended solids or the separation process between solids/colloids and liquid solids. The conclusion in this activity is that the training on making simple water filters can be accepted by local residents to get clean and not cloudy water. It is hoped that with this activity there will be more efforts and willingness from the community to improve the quality of healthy life by paying attention to aspects of the availability and use of clean water